INSOLVENSI DALAM HUKUM KEPAILITAN DI INDONESIA (Studi Putusan No.48/Pailit/2012/Pn.Niaga.Jkt.Pst Antara PT. Telekomunikasi Selular Vs PT. Primajaya Informatika) - Prihatmaka, hervana wahyu; Sunarmi, Sunarmi; Hendra, Rahmad (Lampung University, 2014)
Amendments to the Bankruptcy Law is dominant protect the interests of creditors, because it should be a provision which requires that the debtor should have to go bankrupt. This is contrary to the philosophy of universal bankruptcy. This study aims to determine the bankruptcy provisions in the bankruptcy law in Indonesia and analyze the determination of bankruptcy within the bankruptcy decision No. 48/Bankrupt/2012/PN.NIAGA.JKT.PST. This research is a normative law with normative juridical approach. The data used in this research is secondary data. This study uses literature study with qualitative analysis methods. The authors conclude, first, the provisions of bankruptcy in Indonesia is based on article 2, paragraph (1), which is when the debtor does not repay the debt that will be the bankruptcy estate will go into phase bankruptcy with two possibilities, namely (i) after being declared bankrupt (ii) Through PKPU. Secondly, Award Bankrupt Assets not yet in the stage of bankruptcy because of the Supreme Court overturned the decision of the Commercial Court Decision Number 48/Bankrupt/2012/PN.NIAGA.JKT.PST through decision Number 704K/Pdt.Sus/2012, which ended before the bankruptcy Telkomsel Meeting Debt Verification completed. Advice, first there should be amendments to the Law No. 37 of 2004 specifically test the concept of insolvency and bankruptcy. The authors are aware that this study is not perfect, so the authors hope that further research is done, to continue and resolve the issues raised in this study.Â Keywords: Bankruptcy, Insolvency, the Rule of Law